Adaptive algorithm to compensate varying groupdelay - YANG Zhi-xing; DENG Yong-jun; PAN Chang-yong; SONG Jian (Tongxin xuebao)
A simple and effective adaptive algorithm was proposed to compensate varying group delay in data transmission employing baseband signal processing.Based on the structure of an all-digital parallel receiver（APRX）,the algorithm util-ized the gradient descent（GD）algorithm to iteratively minimize the cost function of constant modulus algorithm（CMA）,and updates the coefficients of group delay compensator.Simulation results show that the group delay can be effectively and adaptively compensated by the proposed algorithm,where the closed eye-diagram is opened successfully.